CHARACTERISTICS OF THE LANDSCAPE CLASSIFICATION SYSTEM OF COMMUNES: CHO RA, BA BE, PHUC LOC, THUONG MINH AND DONG PHUC, THAI NGUYEN PROVINCE - Hoang Duong, Dinh; Thi Hai Yen, Ngo; Van Thanh, Do; Van Hoan, Kieu; Van Manh, Nguyen; Thi Thu Thuy, Vu (HNUE Journal of Science: Journal of Natural Sciences, 2025)
The paper builds a landscape classification system to clarify the characteristics of landscape units in the communes of Cho Ra, Ba Be, Phuc Loc, Thuong Minh, and Dong Phuc, Thai Nguyen province. The diversity and spatial differentiation of the landscape of the area are shown through the model diagram of the landscape classification system; four landscape component maps and landscape (synthesis) maps of the five communes at the same scale of 1:50,000. The landscape units of the area are arranged into a system of seven levels, including one landscape system, one landscape subsystem, one landscape type, three landscape classes, five landscape subclasses, six landscape classes, and one hundred and nineteen types of landscape. The research results provide a database for studies on the use of landscapes for local purposes and a basis to help managers develop planning, orientation for use, and conservation of the landscape here in a reasonable and sustainable way.